International cooperation in the energy sector - Zubko Тетяна (Ius Modernum, 2024)
The influence of international partnership on the stabilization of the state and further development of the energy sector of Ukraine is considered. The main aspects of the integration process of the inclusion of the energy system in ENTSO-T are revealed, the consequences of the changes are investigated, the prospects and challenges of Ukraineʼs energy security are indicated. The purpose of the study is to determine the main influencing factors, threats and prospects for the safe existence and development of the Ukrainian energy industry in the conditions of changing world trends and war. In the course of the study, the hypothesis was tested that in conditions of uncertainty, war and increased globalization, it is the partner assistance from the European Union, with which a single digital space has already been created, that has the greatest impact on the functioning and development of the Ukrainian energy industry. The research used methods of analysis and theoretical generalization, which helped to fulfil the tasks. The state of the energy sector in the conditions of modern changes is highlighted, and the challenges and prospects of supporting and developing the energy sector of Ukraine are indicated.